T1R2 receptor-mediated glucose sensing in the upper intestine potentiates glucose absorption through activation of local regulatory pathways - Kathleen Smith; Elnaz Karimian Azari; Traci E. LaMoia; Tania Hussain; Veronika Vargova; Katalin Karolyi; Paula P. Veldhuis; Juan Pablo Arnoletti; Sebastian G. de la Fuente; Richard E. Pratley; Timothy F. Osborne; George A. Kyriazis (Elsevier, 2018)
Objective: Beyond the taste buds, sweet taste receptors (STRs; T1R2/T1R3) are also expressed on enteroendocrine cells, where they regulate gut peptide secretion but their regulatory function within the intestine is largely unknown. Methods: Using T1R2-knock out (KO) mice we evaluated the role of STRs in the regulation of glucose absorption in vivo and in intact intestinal preparations ex vivo. Results: STR signaling enhances the rate of intestinal glucose absorption specifically in response to the ingestion of a glucose-rich meal. These effects were mediated specifically by the regulation of GLUT2 transporter trafficking to the apical membrane of enterocytes. GLUT2 translocation and glucose transport was dependent and specific to glucagon-like peptide 2 (GLP-2) secretion and subsequent intestinal neuronal activation. Finally, high-sucrose feeding in wild-type mice induced rapid downregulation of STRs in the gut, leading to reduced glucose absorption. Conclusions: Our studies demonstrate that STRs have evolved to modulate glucose absorption via the regulation of its transport and to prevent the development of exacerbated hyperglycemia due to the ingestion of high levels of sugars. Keywords: Glucose homeostasis, Sweet taste receptors, GLP-2, GLUT2, T1R2